POLA PERMINTAAN DAN LOYALITAS PEDAGANG SOTO TERHADAP BIHUN TAPIOKA DI KECAMATAN PURBOLINGGO KABUPATEN LAMPUNG TIMUR - Putriasih, Ni Wayan; Sayekti, Wuryaningsih Dwi; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The objectives of this research were to know demand pattern of tapioca vermicelli and loyalty of soto vendors to tapioca vermicelli. This research was conducted in Purbolinggo Sub District East Lampung District by using cencus method. Data collection was carried out in November 2014-March 2015. The location was chosen purposively. There were 11 villages as research location. Respondents were chosen by using census method. Respondents were all 48 soto vendors using tapioca vermicelli. The method of analysis in this research was descriptive. First purpose was analyzed using descriptive statistics and the second purpose was analyzed using loyalty pyramid. The results showed that demand pattern of tapioca vermicelli has a demand frequency of 30 times per month with the amount of 16-30 kilograms per month. They served soto only with tapioca vermicelli. “Moro Seneng” brand was chosen by most vendors. They usually bought tapioca vermicelli in traditional market. The loyalty level of soto vendors in this research was in the category of liking the brand (97.92%) or categorized as loyal vendors. Key words: demand pattern, loyalty, tapioca vermicelli